GENERATION Z AND PRICE SENSITIVITY: DYNAMIC PRICING STRATEGY AS KEY TO PRODUCT ATTRACTIVENESS - Gunawan Gunawan (Jurnal Ekonomi, 2023)
This study aims to understand how price sensitivity influences Generation Z's preferences and consumption behavior toward products offered in the market, as well as to analyze the most effective pricing strategies in attracting this segment. Using a qualitative approach and descriptive method, data were obtained through in-depth interviews with informants from Generation Z who actively purchase products both online and offline. The findings reveal that Generation Z exhibits high price sensitivity and carefully considers rational aspects before making a purchase, such as comparing prices across marketplaces, looking for free shipping promotions, and evaluating user reviews. They tend to respond positively to transparent and dynamic pricing strategies, as long as they still provide value and fairness in the transaction. Dynamic pricing successfully captures the attention of Gen Z when accompanied by clear communication and reasonable price boundaries. Additionally, Gen Z shows a tendency to be more loyal to brands that can adjust prices according to market conditions without sacrificing quality and integrity. These findings reinforce that adaptive and technology-based pricing strategies play a crucial role in building product appeal and consumer loyalty among Generation Z.